2016
DOI: 10.1080/0376835x.2016.1179104
|View full text |Cite
|
Sign up to set email alerts
|

Performance of land reform projects in the North West province of South Africa: Changes over time and possible causes

Abstract: Anecdotal evidence as well as selected studies on the performance and progress of South

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Considering the long time required for achieving beneficiary capacitation and positive cash flow, IBs might become more inclusive in the future, aligning the implementation scores to the institutional set-up scores. A longitudinal study of IBs seems to be necessary for gaining a better understanding of the empowerment process of the beneficiaries (Kirsten et al, 2016). Recommendations to increase the developmental and transformative impact of IBs are outlined in Chamberlain and Anseeuw (2018).…”
Section: Resultsmentioning
confidence: 99%
“…Considering the long time required for achieving beneficiary capacitation and positive cash flow, IBs might become more inclusive in the future, aligning the implementation scores to the institutional set-up scores. A longitudinal study of IBs seems to be necessary for gaining a better understanding of the empowerment process of the beneficiaries (Kirsten et al, 2016). Recommendations to increase the developmental and transformative impact of IBs are outlined in Chamberlain and Anseeuw (2018).…”
Section: Resultsmentioning
confidence: 99%
“…[27] assessed the link between land reform and poverty reduction in South Africa. Some of the few studies that assessed performance of redistributed farms include [24,[28][29][30]. However, the bulk of studies that assessed the performance of redistributed farms applied a case study approach (looking at specific provinces) [28,30,31].…”
Section: Empirical Literaturementioning
confidence: 99%
“…Kirsten et al [30] found that farming experience, availability of funds, access to markets, and level of technical and financial management skill, among other factors, have a bearing on overall performance of redistributed farms. By the same token, [28] found that technical support is significantly associated with the performance of redistributed farms.…”
Section: Empirical Literaturementioning
confidence: 99%
“…One of the reasons for the failure was based on people who tend to form large groups to access funds to purchase the farm, but in the process bring people who have no farming ambitions. Only few beneficiaries have a passion for farming, while the rest just wait for the benefits (Kirsten et al, 2016). Hence, livelihoods of the farm beneficiaries were not improved.…”
Section: Figure 3 Effectiveness Of Land Reform Programme To Improve Rural Livelihoodsmentioning
confidence: 99%